Short Communication: Lack of a Decline in HIV Incidence in a Rural Community with High HIV Prevalence in South Africa, 2003–2007 - Bärnighausen, Till (Mary Ann Liebert, Inc., 2009)
To understand the dynamics of the HIV epidemic and to plan HIV treatment and prevention programs, it is critical to know how HIV incidence in a population evolves over time. We used data from a large population-based longitudinal HIV surveillance in a rural community in South Africa to test whether HIV incidence in this population has changed in the period from 2003 through 2007. We observed 563 seroconversions in 8095 individuals over 16,256 person-years at risk, yielding an overall HIV incidence of 3.4 per 100 person-years (95% confidence interval 3.1–3.7). We included time-dependent period dummy variables (in half-yearly increments) in age-stratified Cox regressions in order to test for trends in HIV incidence. We first did regression analyses separately for women and men. In both regressions, the coefficients of all period dummy variables were individually insignificant (all p ≥ 0.338) and jointly insignificant (p = 0.764 and p = 0.111, respectively). We then did regression analysis using the pooled data on women and men, controlling for sex and interactions between sex and age. Again, the coefficients of the eight period dummy variables were individually insignificant (all p ≥ 0.387) and jointly insignificant (p = 0.701). We show for the first time that high levels of HIV incidence have been maintained without any sign of decline over the past 5 years in both women and men in a rural South African community with high HIV prevalence. It is unlikely that the HIV epidemic in rural South Africa can be reversed without new or intensified efforts to prevent HIV infection.